PENGARUH BERKUMUR LARUTAN DAUN BINAHONG (Anredera Cordifolia (Ten) Stennis) TERHADAP pH SALIVA PADA SISWA KELAS VII A DAN VII B SMP NEGERI 4 BANJARBARU - putri, elmalia; danan, danan; Bunga Nurwati; Rahmawati, Ida (JURNAL TERAPIS GIGI DAN MULUT, 2024)
Dental caries is a dental and oral health problem that has a fairly high prevalence in the community. The percentage of caries sufferers tends to be high, in children under 18 years old reaching 60-90%. The pH (Potential of Hydrogen) acidity of saliva is one of the important factors that play a role in dental caries. pH control can be done mechanically , namely by gargling. One of the mouthwashes made from natural ingredients is mouthwash from binahong leaves because it contains flavanoids and essential oils that are antimicrobial and antibacterial. This study aims to analyze the effect of gargling with binahong leaf solution (Anredera Cordifolia (Ten) Steenis) on saliva pH in students of grades VII A and VII B of SMP Negeri 4 Banjarbaru. The research is analytical with a type of pseudo-experimental research with a Pretest and Posttest One Group Design research design. The sampling technique is Total Sampling. The results of this study showed that the average pH of saliva before gargling of binahong leaf solution (Anredera Cordifolia (Ten) Steenis) was 6.70, while the average pH of saliva after gargling of binahong leaf solution (Anredera Cordifolia (Ten) Steenis) was 7.08. The results of the Paired T-Test statistical test obtained a value of ρ = 0.000 < α = 0.05. In conclusion, there is an effect of gargling with binahong leaf solution (Anredera Cordifolia (Ten) Steenis) on saliva pH in students of grades VII A and VIII B of SMPN 4 Banjarbaru, which can increase the pH of saliva which was initially acidic to neutral. It is recommended that socialization can be carried out by dental health workers or schools about the use of binahong leaves to maintain dental and oral health and preserve binahong leaf plants through the cultivation program of medicinal plants in schools.